Tree-related Microhabitats and Trees Outside Forest along the Urban-Rural Gradient in Kathmandu Valley - Shrestha, Babita; Sharma, Bhuvan Keshar; Yadav, Ram Kailash Prasad (Journal of Plant Resources, 2022)
Trees Outside Forests (TOF) are found in all strata as urban, suburban and rural. Some TOF serve as Tree Related Micro Habitats (TreMs). We conducted the assessment of TreMs on TOF in Kathmandu valley of central Nepal. Inventory was performed in 209 randomly selected points by Excel using circular plots with 20 m radius. Out of 6210 individuals of 150 tree species recorded from the study area, 1038 TOF of 64 species were found to serve as TreMs. 4 forms, 5 groups and 14 types of TreMs were recorded. Habitat types per tree varied from 1 to 6. 1, 2, 3, 4 and 5 habitat types were found in 665 (64.07 %), 293 (28.23 %), 67 (6.45 %), 8 (0.77 %) and 4 (0.38 %) trees respectively. 6 habitat types were found in one Cinnamomum camphora tree (0.10 %) with 8.60 m height and 75 cm DBH. Out of all the forms, groups and types, all were found in Urban TOF, one type (mistletoe) in suburban TOF and one form (fruiting bodies of saproxylic fungi and slime moulds) along with three types (mistletoe, invertebrate nest and sap run) were absent in rural TOF. The study explored the TreMs on TOF in Kathmandu valley. It provides the baseline data useful for micro habitats as well as biodiversity conservation.